The Future of the United Nations Peacekeeping Force in Cyprus in a Settlement of the Cyprus Conflict - Irabor, Henry Chiedu (Eastern Mediterranean University (EMU), 2010)
ABSTRACT: The main purpose of this thesis is to forecast the future outcome of the United Nations Peacekeeping Force in Cyprus (UNFICYP) based on the Annan Plan and the Boutros Boutros Ghali Set of Idea for Cyprus settlement; presenting an overview of its effectiveness and transition from the past to the present. UNFICYP operation in Cyprus started in 1964 with the United Nations Security Council Resolution 186 (1964) mandating it to carry out a peacekeeping mission. This mission was to control the situation which came as a result of the constitutional change that the then Government of the Republic of Cyprus wanted to implement and which put the Turkish Cypriots on the disadvantageous side in the framework of the 1960 Republic of Cyprus. Since then UNFICYP has been in Cyprus keeping peace and ensuring that the violent uprising of the past did not re-occur again. There is a belief in some quarters that it is the task of UNFICYP to make peace and settlement in Cyprus, however, this falls within the mandate of the UN Secretary General and other officials of the UN who represent the UN in the Cyprus peace talks. The responsibility of UNFICYP is to engender a peaceful environment for peacemaking. To effectively carry out its functions, UNFICYP has gradually metamorphosed from being just a traditional peacekeeping force to a modernized peacekeeping organization. The Annan Plan provided for a peacekeeping force too, but it should have another acronym different from UNFICYP in order to play a complementary role in the implementation of the Cyprus settlements. Keywords: UNFICYP, Annan Plan, UN, Future, Effectiveness. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Bu tezin amaci Kıbrısta bulunan UNFICYP’in (BM barış gücü) geleceğini ön görmek, etkiliğini, getirdiği anlaşmaları ve kuruluğu dönemden bugüne kadar geçişi. UNFICYP Kıbrıstaki harekatına birleşik milletin bariş konseyin 186 kararı ile barışı sağlama adına 1964te basladi. Bu misyon o zamanki Kıbrıs hükümetin anayasa değişikliği ve Kıbrıslı Türklerin 1960 Kıbrıs Cumhuriyeti çerçevesine göre Kıbrıslı Türklerin dezavantajına olusan durumu kontrol etmekti.O gunden beri UNIFICYP Kıbrısta olup barışı sağlamaya çalışması 1960 larda ve 70 lerde ortaya çıkan şiddetli olayların bir daha tekrarlanmaması aynı zamanda uluslararası barış ve düzenine tehdit oluşturmamasıdır.İlginç olarak bazı görüşler UNFICYP’in etkili olamayacağını ve Kıbrıs anlaşmalarında gelecekte hiçbir etkin rol oynamayacağını savunmuşlardır. Bu tez başlıca Rum tarafının karşı çıktığı ve Turk tarafının kabul etttiği Annan Planının temeline bakarak bu düşüncenin aksini savunmuştur.Bazıları UNFICYP’in görevi barışı sağlamak olduğunu düşünüyor.Bu BM Genel sekreteri ve Kıbrıs sorununda BM yi temsil eden görevlilerin işidir.UNFICYP’in sorumluluğu “PİEACEKEEPİNG” yani barışçıl bir ortam sağlamaktır. Bu harekatın başarılı olması için UNFICYP geleneksel bir barış gücünden aktivitesinde barış misyonu önde tutan bir modernliğe geçti.Annan Planı Kıbrıs sorunu çözülmesinde UNFICYP’e önemli rol sağlamıştır. Anahtar Sözcükler: UNFICYP, Annan planı, UN, Gelecek, Etkileyicilik.
Master of Arts in International Relations. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of International Relations, 2010. Supervisor: Assoc. Prof. Dr. Wojciech Forysinski.
Keywords: International Relations; Cyprus - Politics and Government; Cyprus - Cyprus Issue - Peace Negotiations - Peacekeeping - United Nations; Annan, Kofi - The Secretary General of the United Nations - Annan Plan; Diplomatic Negotiations - Cyprus Problem; Cyprus - International Status - International Law; UNFICYP - Annan Plan - UN - Future - Effectiveness